Monuments and monumentality - Silverman, Helaine (1985)
Helaine Silverman shows in this article the complex implications for the archaeological perspective of the relationships between monumental buildings and political-social organization. This theme is developed in the case of the Nasca culture and especially, the monumental site of Cahuachi.